(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The concept of the marginalized has found expression inways more than one in the work of various authors in various ways, most of thembeing autobiographical. The conflict that lies at the base today regarding suchexpression is often considered liable to debate regarding the truthfulness ofexpression, a debate that is more rampant among Indian authors such as OmPrakash Valmiki, who advocate the autobiographical mode of writing saying thatthe oppressed undoubtedly relates to his own life when it comes to delineatingsuffering, as his becomes the epitome of such suppression. However, in casethat the writing is not completely fictionalized does the allegation ofunfeeling upper class writing stand its ground? This is a question worthexploration in Toni Morrison’s Beloved. The novel speaks about theunspeakable atrocities that have been inflicted on the blacks at a time whenautobiographies could hardly contain all the demeaning stances one had beenreduced to merely owing to their skin color. In a case such as this theexperimental mode adopted by Morrison does indeed create a landmark in theexpression of repression of probably the worst kind. The part fictionalizedconcept that finds its way in the work of Morrison is indeed a boon when itcomes to apt expression. The horrors associated with the concept of slaverywhere the condition of humans was far worse than of animals couldn’t findbetter representation than through the use of memory in the most skilfulmanner. Where the presence of the supernatural serves multiple functions, oneof them is the attributing of the unimaginability of the incidents that come tolight owing to the occurrence of the ghost child.